2021
DOI: 10.1109/access.2021.3078823
|View full text |Cite
|
Sign up to set email alerts
|

A Fault Feature Extraction Method for Rolling Bearings Based on Refined Composite Multi-Scale Amplitude-Aware Permutation Entropy

Abstract: Aiming at the problems of unclear early fault characteristics and difficult extraction of rolling bearings, a new nonlinear dynamic analysis method called refined composite multi-scale amplitude-aware permutation entropy (RCMAAPE) is introduced in this paper. Firstly, RCMAAPE is used to extract features from the bearing life data, and Chebyshev's inequality is used to establish a health threshold to evaluate the performance degradation state. Secondly, RCMAAPE is also used for bearing fault diagnosis. Both exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Experimental data. In this case, the bearing vibration data come from the bearing data center of Case Western Reserve University (CWRU) (Lou and Loparo, 2004;Song and Wang, 2021), in which the bearing data acquired at a sampling frequency of 12 kHz are used for analysis. Here, three rotating speeds of 1797 r/min (load 0), 1772 r/min (load 1), and 1750 r/min (load 2) are selected to simulate the bearing operation under variable working conditions, and the vibration data of the three working conditions are marked as Dataset A, Dataset B, and Dataset C, respectively.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…Experimental data. In this case, the bearing vibration data come from the bearing data center of Case Western Reserve University (CWRU) (Lou and Loparo, 2004;Song and Wang, 2021), in which the bearing data acquired at a sampling frequency of 12 kHz are used for analysis. Here, three rotating speeds of 1797 r/min (load 0), 1772 r/min (load 1), and 1750 r/min (load 2) are selected to simulate the bearing operation under variable working conditions, and the vibration data of the three working conditions are marked as Dataset A, Dataset B, and Dataset C, respectively.…”
Section: Experimental Verificationmentioning
confidence: 99%
“…Table 4 shows the main parameters of the CA-YD-186 acceleration sensor. Two clearance states, namely a normal clearance state and a medium-worn state, were tested, using a normal bushing in 0.1 mm clearance and a worn bushing in 0.2 mm clearance [37]. The normal and worn bushings and the connecting rod are shown in Figure 14 The normal bearing clearance vibration signal is shown in Figure 15.…”
Section: Application For Reciprocating Compressor Fault Diagnosismentioning
confidence: 99%
“…Then, we explored the relationship between the GE values and embeddin q. Although the larger the q value, the richer the information obtained after ph construction, a too-large q value is disadvantageous owing to the need of a very 30 q ), which is difficult to meet for a bearing vibration time series [22]. Figure 3 GE values of 1/f noise according to different embedding dimension q values; w with the increase in q value, GE also gradually increases and converges to a worth noting that when q ≥ 3, the fluctuation trend at different nodes no lon This indicates that the GE with embedding dimension q = 3 is sufficient to accu the dynamic changes.…”
Section: The Parameter Selection Of Hgementioning
confidence: 99%
“…Then, we explored the relationship between the GE values and embedding dimension q. Although the larger the q value, the richer the information obtained after phase space reconstruction, a too-large q value is disadvantageous owing to the need of a very large N (10 q -30 q ), which is difficult to meet for a bearing vibration time series [22]. Figure 3 illustrates the GE values of 1/f noise according to different embedding dimension q values; we found that with the increase in q value, GE also gradually increases and converges to about 0.3.…”
Section: The Parameter Selection Of Hgementioning
confidence: 99%
See 1 more Smart Citation